STUDENTS’ SITTING PREFERENCES AT PLAZA IN EDUCATIONAL INSTITUTION - Syam Rachma Marcillia; Diana Kesumasari (Dimensi: Journal of Architecture and Built Environment, 2017)
The purpose of this research is to understand the relationship between sitting preferences and student activities by taking the case of public plaza at the Central Office of the Faculty of Engineering (KPFT) Universitas Gadjah Mada (UGM) in Yogyakarta. KPFT UGM as research object is divided into five zones, namely Zone A (west), Zone B and C (south), and Zone D and E (north). Field observation was done within one month period during working days (weekday) and weekends with observation time: in the morning (08.00-10.00), noon (12-14.00), and afternoon (16.00-18.00). In each of the observation zone, a place-centered mapping was investigated continuously. Informal interview and the questionnaire from 200 students as respondents also undertaken in this research. The results of this study showed that the students’ sitting preferences in the KPFT UGM influenced by the activities that they did. Some of the factors that affect the students’ sitting preferences are: 1) type of activities, 2) the number of people engage in the activity, 3) privacy needs, 4) the needs of the facilities, and 5) the distance between sitting zone in the KPFT UGM and the students’ major buildings.